2019
DOI: 10.1177/1357633x19873239
|View full text |Cite
|
Sign up to set email alerts
|

A cost-consequence analysis comparing patient travel, outreach, and telehealth clinic models for a specialist diabetes service to Indigenous people in Queensland

Abstract: Introduction The delivery of specialist health services to people living in Indigenous communities is an important challenge. Specialist diabetes outpatient clinics may be delivered via a patient travelling to a metropolitan hospital, during an outreach clinic, or by telehealth. The aim of this study was to compare the costs and consequences of different service models for delivering specialist diabetes clinics for a remote Indigenous community. Method Patient travel, outreach and telehealth clinic models were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 23 publications
0
25
0
1
Order By: Relevance
“…This may improve the efficiency of clinics as reduced FTA rates lead to a more productive clinic, with a lower marginal cost per patient attendance. A previous cost analysis of a specialist clinic at the same hospital with similar staffing requirements estimated the average cost of a patient attending at AU$284 for an eight-patient clinic; however, if only five attend, the average cost per patient increases to AU$404, 13 demonstrating that even a small reduction in FTA events could have positive impacts not only for patients and clinicians but also the institution.…”
Section: Discussionmentioning
confidence: 99%
“…This may improve the efficiency of clinics as reduced FTA rates lead to a more productive clinic, with a lower marginal cost per patient attendance. A previous cost analysis of a specialist clinic at the same hospital with similar staffing requirements estimated the average cost of a patient attending at AU$284 for an eight-patient clinic; however, if only five attend, the average cost per patient increases to AU$404, 13 demonstrating that even a small reduction in FTA events could have positive impacts not only for patients and clinicians but also the institution.…”
Section: Discussionmentioning
confidence: 99%
“…attending an appointment. (Smith et al , 2003; Snoswell et al , 2019b). For clinicians, the benefits in terms of reduced time and travel are especially noticeable when care is normally provided through outreach services (Snoswell et al , 2019b; Tousignant et al , 2015).…”
Section: Introductionmentioning
confidence: 99%
“…(Smith et al , 2003; Snoswell et al , 2019b). For clinicians, the benefits in terms of reduced time and travel are especially noticeable when care is normally provided through outreach services (Snoswell et al , 2019b; Tousignant et al , 2015). Additional benefits are increased service efficiencies (Azarmina and Wallace, 2005; Bauer et al , 2019), possible waitlist reduction and avoidance of unnecessary referrals (Caffery et al , 2016; Snoswell et al , 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the implementation of virtual health care practices, hospitals have been able to substantially cut down on costs for both patients and physicians 41 . The benefits of virtual medicine are two-fold: it allows health care workers to be more efficient as time-intensive face-to-face meetings can be addressed virtually, and allows citizens to access lower-cost services 41 . A study conducted in 2017 found that 80.7% of patients experienced a reduction in travel costs due to the Table 2 Common examples of remote patient monitoring technologies.…”
Section: Benefits Of E-healthmentioning
confidence: 99%